2022
DOI: 10.1186/s12985-022-01746-w
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase and tensin homolog gene inserted between NP and P gene of recombinant Newcastle disease virus oncolytic effect test to glioblastoma cell and xenograft mouse model

Abstract: Background Glioblastoma is one of the most serious brain cancer. Previous studies have demonstrated that PTEN function disorder affects the causing and exacerbation of glioblastoma. Newcastle disease virus (NDV) has been studied as a cancer virotherapeutics. In this study, PTEN gene was delivered to glioblastoma by recombinant NDV (rNDV) and translated into protein at the cytoplasm of the glioblastoma. Methods We did comparison tests PTEN protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Many studies have reported that overexpression of PTEN in GBM reduces cell proliferation and increases cell death by inactivating the Akt pathway (31464538, 32445778). We prepared recombinant rNDV using a NDV backbone for PTEN overexpression and used it to infect U87 MG GBM cells; rNDV replication e ciency and PTEM overexpression were con rmed in these cells 9 . Overexpression of PTEN signi cantly decreased the proliferation of U87 MG cells compared with SH-SY5Y neuroblastoma cells (Fig.…”
Section: Overexpression Of Pten Via Ndv Attenuates the Viability And ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have reported that overexpression of PTEN in GBM reduces cell proliferation and increases cell death by inactivating the Akt pathway (31464538, 32445778). We prepared recombinant rNDV using a NDV backbone for PTEN overexpression and used it to infect U87 MG GBM cells; rNDV replication e ciency and PTEM overexpression were con rmed in these cells 9 . Overexpression of PTEN signi cantly decreased the proliferation of U87 MG cells compared with SH-SY5Y neuroblastoma cells (Fig.…”
Section: Overexpression Of Pten Via Ndv Attenuates the Viability And ...mentioning
confidence: 99%
“…The recombinant NDV containing the PTEN gene (rNDV-PTEN) virus was previously constructed 9 . The viruses were propagated by infection of vero cells at an MOI of 0.5 for 2 days.…”
Section: Cell Culture and Cell Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Lytic strains of NDV can infect and kill cancer cells as well as release newly formed progeny viruses 20,21 . The oncolytic effects and mechanisms of several low‐virulence NDV strains have been studied 22–24 . The cancer cell‐killing mechanisms of non‐lytic NDV involve both intrinsic and extrinsic apoptotic pathways and stimulation of immune responses against NDV‐infected cancer cells.…”
Section: Introductionmentioning
confidence: 99%